دراسة قياسية لمنحنى فيليبس في الجزائر خلال الفترة 2020/1990 - عبد الباقي حسناء; شلوفي عمير (جامعة عمار ثليجي الاغواط, 2022)
In this study we tried to drop the first thoughts of Phillips' curve on the Algerian economy for the extended period From 1990-2020 by linking the problem of inflation to unemployment using Augmented ARDL methodology, we have found in This study that there is a long-term balance between unemployment and inflation and thus achieves assumptions Phillips, the developer in the long run, as we came to another conclusion that there was a positive relationship between uunemployment and inflation in the short term because the economic policies pursued by the Algerian authorities It will have a short-term adverse effect on overall balances as high inflation levels and increased Unemployment rates due to uncertainty and uncertainty experienced by economic agents towards these policies.